Development of screen-printed impedance biosensor for characterization of cancer cells - Ahmad Fairuzabadi bin Mohd Mansor (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Electric Cell-Substrate Impedance Sensing (ECIS) is currently gaining widespread application in biomedical field such as cell monitoring. The ability to monitor growth and death of mammalian cells has made this technique more and more popular in drug discovery. Currently chemotherapy treatment subject patients to trial and error therapy, resulting in unoptimized dosage and unnecessary pain for patients. Optimal treatment effectiveness can only be accomplished when the chemotherapy dosage is individualized to each patient. In this study, a silver/silver chloride screen-printed impedance biosensor on glass was developed to characterize A549 lung cancer cell growth in the presence of collagen I, Bovine as substrate coating. The sensor comprise of Interdigital Electrodes Structures (IDEs) with variable spacing. The sensor's optimum spacing between electrodes has been simulated using COMSOL Multiphysics. The sensor was fabricated and incorporated with a culture well made of polydimethylsiloxane (PDMS). A549 cells were cultured in the chambers and impedance measurements were taken at 12 hours intervals for 120 hours. Cell Index (CI) were calculated from the impedance measurement and plotted against time together with the growth profile of the cells using conventional method. A549 cells were also treated with chemotherapy drug; Paclitaxel and its response were monitored over 5 days. Experimental results using biosensor show a similar trend with conventional growth profile of cells in T-flask. Significant reduction in Cell Index (CI) was observed after exposure to Paclitaxel indicating the reliability of the impedance biosensor. Lower spacing between the electrodes has been found to be more sensitive, producing higher Cell Index during cell growth. This work indicates that silver/silver chloride screen printed sensor offers a low cost solution for personalized sensors as it provides a rapid, real time, continuous, reliable method for chemotherapy drug screening.